In Search of Solutions for the Agent Debate - Choudaha, Rahul (International Higher Education, 2013)
The use of agents in international student recruiting is widespread. Using research conducted by World Education Services, this article discusses aspects of the use of agents, pointing to ways that current practices can be improved.